The Relationship Between Emotional Maturity and Procrastination in Writing Thesis Students - Dinda Prihandika Nur Habibah; Siti Nurina Hakim (Prosiding University Research Colloquium, 2022)
The purpose of this study was to determine relationship the Emotional Maturity with Procrastination of Student College Preparing Thesis. The hypothesis is a negative relationship between Emotional Maturity with Procrastination Of Student College Preparing Thesis in Muhammadiyah University of Surakarta. Subjects in this study were 80 subjects. The population used in this study were student college of Psychology Faculty batch 2006 until 2012 Muhammadiyah University of Surakarta and preparing thesis at least one year or two semesters. The measuring instruments used in this study are: a) Scale Emotional Maturity and b) Scale Procrastiation. Data analysis techniques used in this study is the product moment correlation, but because it is not linear then using Spearman's nonparametric statistical techniques. Conclusion The hypothesis of no relationship between Emotional Maturity With Procrastination of College Student Preparing Thesis in Muhammadiyah University of Surakarta. This is indicated by the value of r = -0.105 with sig. 0,178; (p>0.05), it means researchers hypothesis is rejected. Emotional maturity level is high while level of Procrastination in preparation of thesis is classified.